A case report of Dystocia due to shistosomus reflexus (conjoined twins) in a West African Dwarf Doe in Ibadan, Nigeria (2017)
A three years old light brown West African dwarf doe, weighing about 32 kg was presented with history of dystocia of about 36 hours was presented to the University of Ibadan Veterinary Teaching Hospital, Ibadan. The animal was restless. Close observation showed a swollen vulva with protruding foetal head. There was abnormal slimy blood tinted discharges with foul odour in her vulva. Rectal temperature was 40 degree Celcius with relatively high respiratory rate. Dystocia was diagnosed. Using systematic and calculated tration and retropulsion, Schistosomus reflexus (co-joined twins) were subsequently delivered after about 20 minutes of intervention. Post-manipulation care was given by intramuscular injection of procaine penicillin and streptomycin combination at a dose of 1ml per 10kg body weight for 4 days consecutively; multivitamins injection was also given at 1ml per 10kg body weight for four days. Complete recovery of the doe was achieved.